The hybrid aesthetics of the malay vernacular: reinventing classifications through the classicality of South East Asia’s palatial forms - Jahn Kassim, Puteri Shireen; Abdul Majid, Noor Hanita; Md. Sharif, Harlina; Raja Abdul Kadir, Tengku Anis Qarihah (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The paper attempts to re-enact the framework of the ‘vernacular’ of Malay architecture while extending the classifications of its vernacular to include a Classical style ; defined as monumental vernacular expressions representing gradual stylistic changes and ‘hybrid’ constructions throughout the early modernisation period of Malay history which coincides with its evolvement during the Colonial era. During this era, both structural, constructional and ornamental skills absorbed external influences without compromising its vernacular principles. Based on a group of case studies of palatial forms – i.e. palaces and aristocratic houses - from the late 19th and early 20th century, outfired Semper’s anthropological definitions of the essence of the vernacular is used to categorise combinations of masonry and timber in the cases, seen as a manifestation of its heightened aesthetic style. Primarily, the different extents of the ‘base’ or ‘mound’ suggest four basic classifications arising from its construction and technology i.e. (1) the half-column plinth style , (2) the full column and half-plinth stereotomic style (3) the full column-wall stereotomic style; and the (4) the ‘peristyle’ with central stereotomic style. It is argued that the early modern period in the region, coincides with global conditions of ‘neo-classicality ’ and fusion and absorption of new modes and materials of construction . These evolve as new hybrid timber-masonry models that reflecting variants of a Classical-stylistic stream within the vernacular that is a natural consequence of modernity, rising prosperity and a new outlook into the world. By linking these to Semper's definition of the stereotomic and the tectonic, the meaning of the vernacular is extended beyond ‘ the indigenous’ and its typical ‘timber artisanal’ language , into the ‘hybrid’. In doing so, its expands what is generally known as Malay vernacular style to include hybrid variants that reflect the particular era of modernisation of the Malay world. In doing so, expands what is generally known as Malay vernacular architecture to include hybrid variants that reflect the particular era of modernisation of the Malay world.